A new species of the genus Microhyla (Anura: Microhylidae) from Eastern Nepal - Khatiwada, Janak Raj; Shu, Guo Cheng; Wang, Shou Hong; Thapa, Arjun; Wang, Bin; Jiang, Jianping (Zootaxa, 2017)
A new species of the genus Microhyla is described from Jamun Khadi, Jhapa district of eastern Nepal, based on molecular and morphological comparisons. This species is the sister taxon of Microhyla ornata and can be distinguished by a unique vocalization, morphology and molecular phylogeny. The uncorrected genetic divergences based on rRNA gene between the new species and its closest congeners, M. nilphamariensis, M. ornata and M. rubra were 5.34%, 6.67%, and 8.31%, respectively. The new species, Microhyla taraiensis sp. nov., is distinguished from each other of Microhyla by a combination of the following morphological characters: (1) relatively larger body size (SVL ranges 19.9–20.3 mm, n = 4 in the males and 22.1–24.9 mm, n = 3 in the females); (2) dorsal surface of head and body with light red dots; (3) toes webbing poorly developed or absent; (4) a large round inner metacarpal tubercle; and an (5) elongated outer metacarpal tubercle. In addition, our study also provides a new record of Microhyla nilphamariensis from Nepal.